2022
DOI: 10.1155/2022/5262963
|View full text |Cite
|
Sign up to set email alerts
|

HIF-3α-Induced miR-630 Expression Promotes Cancer Hallmarks in Cervical Cancer Cells by Forming a Positive Feedback Loop

Abstract: Purpose. Hypoxia has crucial functions in the development and metastasis of cervical cancer by inducing the expression of numerous genes, including microRNA genes. But we know little about how the hypoxia factors and microRNAs orchestrate to regulate hallmarks of cervical cancer cells. Methods. We conducted RNA sequencing (RNA-seq) and chromatin immunoprecipitation sequencing (ChIP-seq) experiments to investigate the targets of HIF-3α or miR-630. ChIP-qPCR and RT-qPCR were carried out to validate the results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The increased expression of HIF-3α could promote the expression of miR-603, and the high expression of miR-630 could lead to the apoptosis of HeLa cells induced by radiotherapy, while the silencing of miR-630 could accelerate the apoptosis induced by radiotherapy. These results indicate that miR-630 has an anti-radiation function, and the high expression of miR-630 can also promote the expression of HIF-3α, and both have a positive regulatory ring effect ( 70 ).…”
Section: Possible Mechanism Of Resistance To Radiotherapy For Cervica...mentioning
confidence: 93%
“…The increased expression of HIF-3α could promote the expression of miR-603, and the high expression of miR-630 could lead to the apoptosis of HeLa cells induced by radiotherapy, while the silencing of miR-630 could accelerate the apoptosis induced by radiotherapy. These results indicate that miR-630 has an anti-radiation function, and the high expression of miR-630 can also promote the expression of HIF-3α, and both have a positive regulatory ring effect ( 70 ).…”
Section: Possible Mechanism Of Resistance To Radiotherapy For Cervica...mentioning
confidence: 93%
“…One of the factors affecting the transcription of genes responsible for cell adaptation to hypoxia is the hypoxia-inducible factor (HIF). The family of HIF factors includes HIF-1α, HIF-2α, and HIF-3α [ 115 , 116 ]. Gao et al [ 115 ] showed that the increased expression of HIF3α caused by hypoxia increases the expression of the miR-630, and at the same time the increased expression of miR-630 induces overexpression of HIF-3α.…”
Section: Role Of Mirnas In Cervical Cancermentioning
confidence: 99%
“…The family of HIF factors includes HIF-1α, HIF-2α, and HIF-3α [ 115 , 116 ]. Gao et al [ 115 ] showed that the increased expression of HIF3α caused by hypoxia increases the expression of the miR-630, and at the same time the increased expression of miR-630 induces overexpression of HIF-3α. Thus, a feedback loop between miR-630 and HIF-3α has been demonstrated.…”
Section: Role Of Mirnas In Cervical Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…It is overexpressed in multiple types of cancers, including osteosarcoma, ovarian, colorectal, bladder, hepatic, gastric, and renal cancers [12][13][14][15][16][17][18][19]. In these contexts, miR-630 functions as an oncomiR by promoting cell proliferation, migration, invasion, and increasing chemoresistance or radioresistance [20][21][22][23][24][25][26]. Conversely, miR-630 has also been reported as a tumor suppressor, as shown by the downregulation in tumors and inhibiting cancer aggressiveness in several types of cancer, such as esophageal, breast, glioma, and lung [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%